Pelatihan Aplikasi Talent Identification (TID) Cabang Olahraga Atletik Pada MGMP PJOK Kabupaten Jayapura - Saharuddin Ita; Ansar CS; Ipa Sari Kardi; Muh. Syaiful Syam (Pusat Riset dan Inovasi Nasional, 2023)
This service aims to increase the knowledge and skills of Physical Education teachers (PJOK) in identifying the athletic talents of their students by using the Identification of Special Athletic Talents (TID) application. The partner institution is the MGMP PJOK SMP in Jayapura District. The methods used include seminars and training sessions. Data collection techniques include observation and evaluation of training results, with data analysis through pretest and posttest evaluations. The results of this dedication are as follows: (1) Most of the participants were not familiar with the Athletics-specific Talent Identification (TID) application before the training, and (2) Quite a number of participants understood and were proficient in using the Athletics-Talent Identification (TID) application. especially after getting explanations and hands-on practice. The conclusions drawn from this dedication are: (1) Substantially increasing the knowledge and skills of the MGMP PJOK SMP related to the use of the Special Athletic Talent Identification (TID) application for athletics, (2) The establishment of collaboration between FIK UNCEN and MGMP SMP PJOK in Jayapura Regency, and (3) The successful implementation of community service as a lecturer's academic task.